Nigerian Students’ Information Needs and Behaviour when Seeking Information at NIMS University in Jaipur, India (American Journal of Interdisciplinary Research and Innovation, 2023)
The study’s goal was to figure out the Nigerian students at NIMS University, Jaipur information-seeking behaviour, and needs. In this study, a survey research approach was utilized. The sample population was chosen using a random sampling technique. To collect data, a structured, closed-ended questionnaire was distributed to 100 students from Nigeria who are enrolled in the School of Humanities, Social Science, and Commerce. 91 of the 100 questionnaires that were distributed to 25 female and 75 male Nigerian students were completed and returned successfully. The study looks at three distinct programmes: B.Sc., MSc/MLIsc., and Ph.D. According to the study’s findings, research scholars require information in order to write research articles about immigration and study programmes for Nigerian students. According to the study, the majority of Nigerian students and researchers to find information, use electronic resources like databases and electronic journals and books. Nigerian students, according to the findings, do not frequently use the library because of the language barrier.